Biosocial Research in Social Work Journals: A Systematic Review. (February 2018) - Maynard, Brandy R.; Boutwell, Brian B.; Vaughn, Michael G.; Naeger, Sandra; Dell, Nathaniel
Background: Despite an emphasis on a biopsychosocial understanding of human behavior and the relevance of biosocial research to social work practice, it is unclear whether social work is contributing to biosocial research and knowledge. Methods: Systematic review procedures were employed to locate studies that included biological variables (e.g., genetic or physiological factors) related to behavior and were published in a social work journal between 2000 and 2015. Seventy-five social work journals were searched. Studies were screened and coded by two independent reviewers. Results: Eleven studies were eligible for this review; one was a behavior genetics study, two were molecular genetics studies, two were neurological studies, and six studies examined physiological factors such as skin conductance and salivary cortisol. Discussion: Findings suggest that social work as a discipline is not contributing new knowledge to advance the "bio" component of the biopsychosocial framework. Implications and recommendations are discussed.